Pengembangan Sistem Informasi Penjadwalan dan Monitoring Backup Data Berbasis Web: (Studi Kasus PT. Pupuk Sriwidjaja Palembang) - Sahfitri, Vivi; Saputra, Dirut (Jurnal Ilmiah Matrik, 2024)
This research aims to facilitate the admins of the Business Partner Department and IT Services at PT. Pupuk Sriwidjaja Palembang in searching for data, backing up data, and scheduling data in an organized manner. To support this convenience, the author has developed a web-based infrastructure backup data portal system, utilizing a MySQL database. This system can be used to manage network data, website data, as well as data reports or archives. The research method employed is the Waterfall method, which consists of several stages: analysis, design, implementation, testing, and maintenance. Data collection methods included interviews and observations. The result of this research is a website that enhances the performance of the admins of the Business Partner Department and IT Services at PT. Pupuk Sriwidjaja Palembang in managing company data.